Association of serum ADAMTS7 levels and genetic variant rs1994016 with acute coronary syndrome in a Chinese population: A case control study. (August 2018) - Lin, Yan; Chen, Han; Wang, Yidong; Jin, Chunna; Lin, Xiaoping; Wang, Cuncun; Lu, Yi; Chen, Zexin; Wang, Jian-an; Xiang, Meixiang
Abstract: Background and aims: Acute coronary syndrome (ACS) is commonly caused by rupture or erosion of coronary atherosclerotic plaques and secondary thrombus formation. Metalloproteinase ADAMTS7 was found to play an important role in atherogenesis. This study aimed to explore the association of serum ADAMTS7 levels and rs1994016 polymorphism at ADAMTS7 locus with ACS in a Chinese population. Methods: 1881 patients who underwent coronary angiography were consecutively recruited. Among them, 426 patients were matched for case-controlled analysis. Serum ADAMTS7 levels were determined through enzyme-linked immunosorbent assay (ELISA) and rs1994016 polymorphism was detected by polymerase chain reaction (PCR). Results: Serum ADAMTS7 levels in patients with unstable angina pectoris were much higher than in non-atherosclerotic patients, however, no difference was found among non-atherosclerotic patients, the coronary atherosclerosis subgroup and stable angina pectoris subgroup. A higher serum ADAMTS7 level was found in the ACS group than in the non-ACS group (0.61 ± 0.04 vs. 0.47 ± 0.02 ng/mL, p = 0.002) and serum ADAMTS7 level was found to be an independent risk factor for ACS after adjusting for major confounding factors (OR:2.81, 95% CI:1.33–5.93, p = 0.007). ADAMTS7 rs1994016 CT/TT polymorphism was negatively associated with the risk of ACS (OR:0.40, 95% CI:0.22–0.71, p = 0.002). Meanwhile, crossover analysis revealed that in CT/TT homozygotes, ACS risk was reduced nearly 80% in patients with serum ADAMTS7 levels <0.594 ng/mL (Interaction p = 0.002). Conclusions: Serum level of ADAMTS7 was positively associated and rs1994016 CT/TT genotype was negatively associated with the risk of ACS. Patients with lower serum ADAMTS7 level and rs1994016 CT/TT genotype are less likely to suffer from ACS in a Chinese population. Highlights: Serum ADAMTS-7 level is an independent factor of ACS. rs1994016 CT/TT genotype has negative association with ACS. Lower serum ADAMTS-7 level with rs1994016 CT/TT genotype is less vulnerable to have ACS. Indicate the role of ADAMTS-7 in the stability of coronary atherosclerotic plaque. Examine the role of ADAMTS-7 by combining genetic and protein levels together.